2017
DOI: 10.1186/s13173-017-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Detecting referential inconsistencies in electronic CV datasets

Abstract: One way to measure the scientific progress of a country is to evaluate the curriculum vitae (CV) of its researchers. In Brazil, this is not different. The Lattes Platform is an information system whose primary objective is to provide a single repository to store the CV of the Brazilian researchers. This system is increasingly acquiring expressiveness as the main source of information regarding the Brazilian community of researchers, students, managers, and other actors in the national system of science, techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The figures were lower for all document types and much lower in the arts & humanities, 50% for journal citable items and just 20% for books and book chapters. Articles published in regional publications may also be less associated with DOIs, a sample of scholars from Brazil showed DOIs among less than half of their journal papers and less than a tenth of their conference papers (Rubim & Braganholo, 2017). Meanwhile, Mugnaini et al (2021) found the presence of international co-authors increased the proportion of DOIs.…”
Section: Limitations Of Doi Accuracymentioning
confidence: 99%
“…The figures were lower for all document types and much lower in the arts & humanities, 50% for journal citable items and just 20% for books and book chapters. Articles published in regional publications may also be less associated with DOIs, a sample of scholars from Brazil showed DOIs among less than half of their journal papers and less than a tenth of their conference papers (Rubim & Braganholo, 2017). Meanwhile, Mugnaini et al (2021) found the presence of international co-authors increased the proportion of DOIs.…”
Section: Limitations Of Doi Accuracymentioning
confidence: 99%